THE FACTOR ANALYSIS THAT INFLUENCE THE STUDENT PURCHASE INTENTION IN SHOPEE E-COMMERCE - Nursyirwan, Vivi Iswanti; Ardaninggar, Sasmita Sari (EAJ (Economic and Accounting Journal), 2020)
The purpose of this research was to analyze the effect of Promotion, Website Quality and Trust on Purchase Intention in Shopee's e-commerce. The study employed purposive sampling with certain criteria and iteration formulas so that the number of samples obtained was 100 samples of Shopee e-commerce users from undergraduate students of The Economic Faculty of Pamulang University as respondents. By using Structural Equation Modeling with Partial Least Square Approach, the results indicated: (1) the promotion had positive and significant on  purchase intention; (2) promotion had positive and significant on consumerâ€™s trust; (3) The results showed that between variables there was no significant influence between consumerâ€™s trust and purchase intention; (4 and 5) Website quality had a positive and significant influence on both purchase intention and consumerâ€™s trust. However, (6 and 7) Both the promotion and website quality had no significant influence to purchase intention with consumerâ€™s trust as intervening.